A novel single‐layer quasi‐self‐complementary element for broadband reflectarray antennas. Issue 12 (23rd August 2021) - Ning, Peng; Zhu, Hong; Guo, Lu; Feng, Wenjie
Abstract: A broadband single‐layer reflectarray adopting quasi‐self‐complementary (QSC) elements is studied and developed. The unit cell is formed by a strip in an inverted L shape and a slit also in an inverted L shape etched within a rectangular patch, constituting a QSC configuration. By varying the length of the QSC structure, a rather linear phase range of 370° is achieved, resulting in a broadband characteristic. Employing the novel unit cell, a reflectarray containing 529 elements and offset fed is proposed at 10 GHz. Experiment results present a superior behavior of the reflectarray, including a large 38% bandwidth for a gain drop of 1‐dB, a 59% peak aperture efficiency, and a 28 dB cross polarization discrimination at 10 GHz, respectively.